STUDI EKSPLORASI FAKTOR PENENTU PENILAIAN HARGA SAHAM PT SEMEN INDONESIA (PERSERO) TBK - Anggraini, Kafita; Hayati, Nur (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This research explores the share price performance of PT Semen Indonesia (Persero) Tbk from 2019 to 2023 using descriptive analysis methods. The research focus includes variables such as Earnings Per Share (EPS), Debt to Equity Ratio (DER), Total Asset Turnover (TATO), Return on Equity (ROE), Current Ratio (CR), Price Earning Ratio (PER), and Net Profit Margin (NPM). The data used comes from the annual financial report of PT Semen Indonesia. Research findings show that the company experiences significant fluctuations in EPS which are influenced by sales dynamics and operational costs.ROE shows variations in the efficiency of using own capital, while DER decreases consistently, reflecting good management in debt management. TATO and ROA experienced fluctuations, reflecting the company's efforts to optimize the use of assets to increase operational efficiency. The company's liquidity, as reflected in the CR remains stable in meeting short-term obligations. Even though PER has decreased, indicating a lower market assessment of share valuation, NPM varies due to fluctuating operational costs. To improve stability and profitability in the future, the company's focus needs to be increased on operational efficiency and better cost management